Anatomy and relationships of forelimb lymph nodes in Sprague-Dawley rats: A detailed dissecting approach - Chen, Linhai; Yang, Jing; Kim, Sang Ah; Gelvosa, Ma. Nessa; Wei, Peng; Jeon, Jae Yong; Cheon, Hwayeong (Frontiers in Veterinary Science, 2022)
Background: Constructing a reliable animal model for preclinical treatment of secondary lymphedema is challenging because the anatomical characteristics near the lymph nodes are understudied. Therefore, this study examined the detailed anatomical relationship between the axillary lymph node flaps (ALNFs) and brachial lymph node flaps (BLNFs) in the forelimb of Sprague-Dawley (SD) rats. Materials and Methods: Ten male rats, weighing 250–300 g, were used. The ALNFs and BLNFs on either side of the rat forelimbs were dissected. The two lymph node flaps (LNFs) were immediately harvested to analyze their physical characteristics (via imaging process software) and microscopic structure (via histology examinations). Results: A total of 20 ALNFs and BLNFs from 10 rats were harvested and analyzed. ALNF dissection was simpler and lasted a shorter time than BLNF dissection (p < 0.0001). The left LNFs were more difficult to dissect than the right LNFs (p < 0.0001). In physical characteristics of LNFs, the area (p < 0.001) of LNFs and the number of lymph nodes (p < 0.0001) associated with ALNFs were greater than those associated with BLNFs, but the pedicle lengths of ALNFs were shorter than that of BLNFs (p < 0.0001). No significant difference in the diameter of the venous and arterial pedicles was noted between the two LNFs (p > 0.05). Conclusion: This study reported detailed physical characteristics of ALNFs and BLNFs in SD rat forelimbs, assessing the respective area of LNFs, number of lymph nodes, and lengths and diameters of vascular pedicles. Moreover, this study suggested an efficient method to perform a study of LNFs by describing the operation process and repeatedly measuring the operation time.